Reassessment of the human mandible from Banyoles (Girona, Spain). Issue 174 (January 2023) - Keeling, Brian A.; Quam, Rolf; Martínez, Ignacio; Arsuaga, Juan Luis; Maroto, Julià
Abstract: Since the discovery of a human mandible in 1887 near the present-day city of Banyoles, northeastern Spain, researchers have generally emphasized its archaic features, including the lack of chin structures, and suggested affinities with the Neandertals or European Middle Pleistocene (Chibanian) specimens. Uranium-series and electron spin resonance dating suggest the mandible dates to the Late Pleistocene (Tarantian), approximately ca. 45–66 ka. In this study, we reassessed the taxonomic affinities of the Banyoles mandible by comparing it to samples of Middle Pleistocene fossils from Africa and Europe, Neandertals, Early and Upper Paleolithic modern humans, and recent modern humans. We evaluated the frequencies and expressions of morphological features and performed a three-dimensional geometric morphometric analysis on a virtual reconstruction of Banyoles to capture overall mandibular shape. Our results revealed no derived Neandertal morphological features in Banyoles. While a principal component analysis based on Euclidean distances from the first two principal components clearly grouped Banyoles with both fossil and recent Homo sapiens individuals, an analysis of the Procrustes residuals demonstrated that Banyoles did not fit into any of the comparative groups. The lack of Neandertal features in Banyoles is surprising considering its Late Pleistocene age. A consideration of the Middle Pleistocene fossil record in Europe and southwest Asia suggests that Banyoles is unlikely to represent a late-surviving Middle Pleistocene population. The lack of chin structures also complicates an assignment to H. sapiens, although early fossil H. sapiens do show somewhat variable development of the chin structures. Thus, Banyoles represents a non-Neandertal Late Pleistocene European individual and highlights the continuing signal of diversity in the hominin fossil record. The present situation makes Banyoles a prime candidate for ancient DNA or proteomic analyses, which may shed additional light on its taxonomic affinities.